Penerapan Metode Dempster Shafer Dalam Mendeteksi Kerusakan Mesin Air Berbasis Android - Afrilia, Yolanda; Sembiring, Abdul Sani; Hutabarat, Hukendik (JURIKOM (Jurnal Riset Komputer), 2018)
Many people do not understand the water damage, so tend to use the technician regardless of the damage. What's more to the present day many people do things quickly and accurately? Treatments that would be done alone without having to come to the service is very helpful at all for everyday life. The expert system is one of the artificial intelligence systems that contain the knowledge and experience that one expert puts into one particular area each person can use to solve a specific problem. In this case, water span range occurs in daily life. In this thesis will be discussed on how to find damage to the water machine by applying the Dempster-Shafer method. This method is used to search for evidence based on belief functions and plausible reasoning used by combining separate information (evidence) pottery to calculate the possibility of a malfunction.